Strengthening Teacher Responsibility towards Islamic Education In Ibtidaiyah Madrasah at Kasih Sayang Foundation - isnawati; Muhammad Sapii Harahap; Susidamaiyanti; Al Misry; Abidah (Community Development Journal, 2022)
A phenomenon that has been seen during the fact that most teachers do not carry out their obligations as they should due to having different educational backgrounds, the ability of children who are lacking with a background low socioeconomics and demands on the fulfilment of administrative completeness as a teacher receiving a professional certification. This activity aims to strengthen the responsibility of teachers as a profession, especially religious teachers.  This method of service activity uses a   Participation Action Research (PAR) approach through socialization, training and mentoring to teachers, especially in aspects of faith, morals, physical, and intellectual improvement of students,  student psychology and society. The target of this activity is the total number of teachers who teach Ibtidaiyah Madrasah at The Kasih Sayang Foundation, which is  20 teachers.  The instrument in this activity uses a pre and post-test questionnaire while the difference test uses a Wilcoxon test with p = 0.001. There is a change in the   responsibility  of teachers of Islamic religious education after this activity ends